A Scoping Review of the Associations Between Sense of Belonging and Academic Outcomes in Postsecondary Education - Fong, Carlton J.; Adelugba, Semilore F.; Garza, Melissa; Pinto, Giovanna Lorenzi; Gonzales, Cassandra; Zarei, Pedram; Rozek, Christopher S. (Educational psychology review, 2024)
Given the theorized importance of college belonging for academic success, we conducted a scoping review of studies examining relationships between sense of belonging and academic achievement and persistence for postsecondary students. In our scoping review, we included 69 reports (78 unique samples) published between 2003 and 2023. We observed an unexpected level of heterogeneity among the associations between belonging and academic outcomes (GPA, persistence, and intent to persist); most associations were positive but small with several small, negative associations. Across a few studies, there was a pattern of larger associations between belonging and academic achievement for marginalized college students, such as racially/ethnically minoritized students (compared to students in the racial majority) or women (compared to men) in historically exclusionary settings such as STEM disciplines. We identified gaps in the literature reflecting underreporting of student identities, including but not limited to gender identity, sexual identity, social class, religious identity, disability status, and first-generation status, in sample characteristics and a lack of attention to contextual factors, such as the type of institution (e.g., predominantly White institutions, community colleges, minority-serving institutions). In all, our findings provide an updated mapping of the literature, pointing to a much-needed refinement for how individual and institutional factors may moderate the associations between belonging and academic outcomes in postsecondary settings.